Failing victims? Challenges of the police response to human trafficking. Issue 3 (31st July 2019) - Farrell, Amy; Dank, Meredith; de Vries, Ieke; Kafafian, Matthew; Hughes, Andrea; Lockwood, Sarah
Abstract : Research Summary: The police have a duty to provide assistance to crime victims. Despite the importance of this role, scholars examining police effectiveness have historically been less attentive to the needs of victims. As the police are increasingly called on to combat sex and labor trafficking crimes, it is timely to explore how this new population of victims is served by the police. Information from a review of human trafficking investigations and in‐depth interviews with police and service providers in three U.S. communities indicates that human trafficking victims often do not trust the police and rarely seek their assistance. When the police do respond, human trafficking victims seek affirmation of their experiences and safety from future harm. Policy Implications: Recommendations are offered to improve police responses to human trafficking victims including efforts to build trust, promote victim safety, and meet the needs of victims outside of the justice system.